Expression of CD2 on porcine B lymphocytes - Sinkora, J; Reháková, Z; Sinkora, M; Cukrowska, B; Tlaskalová-Hogenová, H; Bianchi, A T; De Geus, B (Immunology, 1998)
Remarkable interspecies differences in CD2 expression on B lymphocytes have been reported in mammals. Human and rat B cells lack CD2, whilst B lymphocytes in mice are CD2+. In pigs, B cells have been supposed not to express CD2. We show here, however, that CD2 is present at a low level on a prominent subset of porcine B cells. Moreover, we describe changes in the proportions of CD2+ and CD2- B-cell subsets during ontogeny. Before contact with microflora, the majority of peripheral surface immunoglobulin M+ (sIgM+) B cells express CD2 and sIgM+CD2- B cells are rare. Shortly after colonization of conventional (CV) piglets with complex intestinal microflora, numerous CD2- B cells appear in the periphery and their relative number increases with age in both CV and specific pathogen-free (SPF) pigs. However, monoassociation of germ-free (GF) piglets with a single Escherichia coli strain does not result in a significant increase of sIgM+CD2- B cells in the periphery. We suggest that CD2 is down-regulated in porcine B lymphocytes upon activation with microflora in mucosa-associated lymphatic tissues. In bone marrow (BM), we identified putative porcine B-cell precursors. These cells express CD2 at low density and do not bear either the common myelomonocytic antigen or T and B-lymphocyte receptors. Similar to mouse and human pre-B cells, this lymphocyte-sized subset expresses CD25 and class II antigens. CD2 positivity of these cells indicates that CD2 is expressed earlier than sIgM during B lymphopoiesis in pigs.
Keywords: Antigens, Differentiation; Aging; Immunophenotyping; průtoková cytometrie; imunofenotypizace; Cell Differentiation; Intestines; CD2 Antigens; leukocyty mononukleární; B-Lymphocyte Subsets; podskupiny B-lymfocytů; kostní dřeň; gnotobiologické modely; střeva; diferenciační antigeny; Flow Cytometry; Swine; stárnutí; antigeny CD2; ženské pohlaví; zvířata; Germ-Free Life; Escherichia coli Infections; prasata; buněčná diferenciace; Bone Marrow; Female; Leukocytes, Mononuclear; infekce vyvolané Escherichia coli; Animals